Community program: warga berilmu dan sihat di usia emas (WISE) - Kamaruddin, Khairatul Nainey (Faculty of Medicine, 2022)
On 12th Jun 2022 and 26th Jun 2022, WISE' program initiated by the Primary Care Medicine in collaboration with ICAN, Dentabay Dental Clinic, and Pusat Aktiviti Warga Emas (PAWE) held at the Dewan Pinang. This program to help the elderly community to achieve this successful and healthy aging. ‘WISE’. This program educates and create awareness among the elderly community in Selangor's urban and sub-urban areas about chronic diseases, frailty, and healthy lifestyle. It started with careful planning by the team members, headed by Dr. Nafiza Mat Nasir as the program director. This events gathered a total of 60 participants from various socioeconomic backgrounds.